Pigmentos híbridos orgânicos/ inorgânicos derivados em argilominerais a partir de diferentes rotas de síntese - Cavalcanti, Graycyellê Rodrigues da Silva (2021)
Pigments has historical and cultural importance in the society, while technological advances improved the preparation of more stable and versatile systems with sophisticated applications than those used in industry or in the art objects. Therefore, the present work aimed to prepare organic/inorganic hybrid pigments based on the interaction between raw and modified silicates and archeological dyes (carminic acid and eosin Y) and a photochromic molecule as spiropyran type. Systems were evaluated by different techniques as X-rays diffractometry (XRD), 13C nuclear magnetic resonance (NMR), time-resolved fluorescence and UV-Vis spectroscopy. Stability and potential applications of the formed pigments were also evaluated. 13C NMR and fluorescence results of the pigment for the aluminum oxide pillarized saponite showed that the pillarization improved the stability of the pigment based on carminic acid. The formation of stable pigments obtained by carminic acid encapsulation in saponite and montmorillonite precursor hydrogels was confirmed by photostability tests. The results of UV-Vis spectroscopy and thermogravimetry for eosin Y derivatives indicated that the smectites silylation with aminopropyltrimethoxysilane improved their interaction with eosin Y. The colorimetric parameters suggested the formation of stable pigments with different colors. In the study of the application of spiropyran (SPI) as an intelligent pigment, the results of the colorimetric tests showed that the prepared pigments presented a color palette from violet to yellow with relative stability after light irradiation and photoreversible capacity. XRD pattern ssuggested that the SPI incorporation occurred by intercalation and the pigments obtained via hydrolysis did not form a crystalline phase. In summary, the preparation of proposed hybrid pigments resulted in multifunctional materials and improved their properties for use in art objects, but also as sensors and in photovoltaic cells.